A plea for extension of the anatomical nomenclature: Vessels - Kachlik, David; Musil, Vladimir; Blankova, Alzbeta; Marvanova, Zuzana; Miletin, Jakub; Trachtova, Daniela; Dvorakova, Vlasta; Baca, Vaclav (Bosnian journal of basic medical sciences, 2021)
This article is the fourth and last part of a series aimed at extending and correcting the anatomical nomenclature. Because of the rapid development of internet and the use of electronic formats in communication in anatomy, embryology, histology, medical education, and clinical medicine, an appropriate, precise, and concise anatomical nomenclature is required. Such tool enables to avoid any potential confusion and possible scientific/medical mistakes. The up-to-date official anatomical terminology, Terminologia Anatomica, is available longer than 20 years and needs to be refined and extended. The authors have collected and listed 210 terms and completed them with definitions and/or explanations. We aimed to start a discussion about their potential incorporation into the new revised version of the Terminologia Anatomica. This article is primarily focused on the vessels of the human body (arteries, veins, and lymphatic system).
Keywords: anatomie; Terminology as Topic; Anatomy; cévy; Humans; lidé; terminologie jako téma; Blood Vessels